Partial differential equations (with 42 illustrations) - Jeffrey Rauch (Spriger-Verlag, 1991)
This book presents an introduction to the ideas, phenomena, amd methods from partial differential equations. It includes elliptic, hyperbolic, and parabolic equations, the energy method, maximum principle, and the Fourier transform. It features many historical and scientific motivations and applications. Included throughout are exercises, hints, and discussions that form an important and integral part of the book